SEMANTIC ANALYSIS OF SYNONYMS IN ARABIC: DIFFERENCES IN CLASSICAL AND MODERN TEXTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the semantic analysis of synonyms in classical and modern Arabic texts. The study explores the differences in meaning, contextual usage, and semantic evolution of synonyms over time. It compares the richness of meaning in classical Arabic literature with the simplification trends observed in modern texts. The research aims to identify key differences that influence the stylistic and cultural characteristics of texts, shedding light on the linguistic evolution of synonyms. The findings contribute to understanding the dynamics of Arabic language development and its application in contemporary contexts.